2017
DOI: 10.1016/j.wneu.2017.03.088
|View full text |Cite
|
Sign up to set email alerts
|

First Application of 7-T Magnetic Resonance Imaging in Endoscopic Endonasal Surgery of Skull Base Tumors

Abstract: Background Successful endoscopic endonasal surgery for the resection of skull base tumors is reliant on preoperative imaging to delineate pathology from the surrounding anatomy. The increased signal-to-noise ratio afforded by 7T MRI can be used to increase spatial and contrast resolution, which may lend itself to improved imaging of skull base. In this study, we apply a 7T imaging protocol to patients with skull base tumors and compare the images to clinical standard of care. Methods Images were acquired at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 48 publications
(60 reference statements)
1
7
0
Order By: Relevance
“…de Rotte et al first reported the feasibility of pituitary imaging at 7 T MRI. 9 Barrett et al, who qualitatively compared 7 T versus conventional MRI in a preliminary set of skull base patients, confirmed improved detection rates of internal carotid artery (ICA) branches and cranial nerves (CNs) at 7 T. 14 Most recently, Law et al reported results from a microadenoma in one Cushing's patient who was MRI negative at conventional field strength but visible at 7 T in a location that correlated with petrosal sampling and postoperative outcome. 15 Early reports suggesting feasibility and benefits of ultra-high field MRI over lower field techniques in pituitary pathology have been limited by small sample sizes and inability to statistically compare 7 T to lower field scans.…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…de Rotte et al first reported the feasibility of pituitary imaging at 7 T MRI. 9 Barrett et al, who qualitatively compared 7 T versus conventional MRI in a preliminary set of skull base patients, confirmed improved detection rates of internal carotid artery (ICA) branches and cranial nerves (CNs) at 7 T. 14 Most recently, Law et al reported results from a microadenoma in one Cushing's patient who was MRI negative at conventional field strength but visible at 7 T in a location that correlated with petrosal sampling and postoperative outcome. 15 Early reports suggesting feasibility and benefits of ultra-high field MRI over lower field techniques in pituitary pathology have been limited by small sample sizes and inability to statistically compare 7 T to lower field scans.…”
Section: Introductionmentioning
confidence: 96%
“…15 Early reports suggesting feasibility and benefits of ultra-high field MRI over lower field techniques in pituitary pathology have been limited by small sample sizes and inability to statistically compare 7 T to lower field scans. 9,14 Furthermore, the utility of 7 T MRI has not been quantitatively examined in a homogenous cohort of pituitary adenoma patients. The purpose of the present study was to acquire preoperative 7 T MRI and quantitatively compare detailed neuroradiological findings for pituitary adenomas and adjacent skull base neurovascular structures to conventionl MRI.…”
Section: Introductionmentioning
confidence: 99%
“…Details of the sequences are available in Table 2 . This protocol was optimized for detection of epileptogenic foci by reference to literature [ 18 , 19 , 25 , 26 , 28 , 29 , 32 ] and in consultation with a CAQ neuroradiologist (BD) [ 37 , 38 ].…”
Section: Methodsmentioning
confidence: 99%
“…However, multiple authors have also conceded that susceptibility artifacts near large air-tissue interfaces and the skull base could compromise the utility of 7T in some patients. 8,10 MR imaging at 7T may also assist in identifying parenchymal areas with an increased likelihood of microscopic high-grade glioma infiltration, which is challenging at clinical field strengths and important for determining resection margins. 11 Various imaging metrics, including those based on DWI, have been used to identify white matter infiltration by gliomas that cannot be resolved at lower field strengths.…”
Section: Intracranial Tumorsmentioning
confidence: 99%
“…de Rotte et al 17 were the first to demonstrate the feasibility of pituitary adenoma imaging at 7T; however, their study did not report on vascular sequences. Barrett et al 10 used a semiquantitative rating system to demonstrate superior visualization of internal carotid artery branches and vasculature within skull base tumors using 7T TOF, despite higher B 0 and B 1 inhomogeneity artifacts at 7T. It does appear that TOF could benefit surgical navigation to minimize vascular injury during endoscopic pituitary surgery (Fig 1).…”
Section: Intracranial Tumorsmentioning
confidence: 99%